Singular value determination for IR-UWB radar sensor-based human motion detection - Terence Jerome Daim; Razak Mohd Ali Lee (2021)
Human motion detection is a method of identification where various techniques and equipment are combined to distinguish human motion. Recently, recognition with IR-UWB radar sensor has become an exciting area of study. The output data in its original form, without any processing as produced by the IRUWB radar sensor, cannot have a singular value to be used to differentiate the fast and slow movement of a human hand. There is, therefore, a need for an output data processing algorithm that generates the required singular value. This paper proposes a method for evaluating the singular value based on the original output data produced by the sensor to accurately classify human motion in fast and slow movement of the human hand. The results of the proposed method are encouraging in which fast and slow hand movement can be distinguished accurately.